Mandibular Branch of the Facial Nerve in Wistar Rats: New Experimental Model to Assess Facial Nerve Regeneration - Bento, Ricardo Ferreira; Salomone, Raquel; Nascimento, Silvia Bona do; Ferreira, Ricardo Jose Rodriguez; Silva, Ciro Ferreira da; Costa, Heloisa Juliana Zabeu Rossi (International Archives of Otorhinolaryngology, 2014)
Introduction The ideal animal model for nerve regeneration studies is the object of controversy, because all models described by the literature have advantages and disadvantages.Objective To describe the histologic and functional patterns of the mandibular branch of the facial nerve of Wistar rats to create a new experimental model of facial nerve regeneration.Methods Forty-two male rats were submitted to a nerve conduction test of the mandibular branch to obtain the compound muscle action potential. Twelve of these rats had the mandibular branch surgically removed and submitted to histologic analysis (number, partial density, and axonal diameter) of the proximal and distal segments.Results There was no statistically significant difference in the functional and histologic variables studied.Conclusion These new histologic and functional standards of the mandibular branch of the facial nerve of rats establish an objective, easy, and greatly reproducible model for future facial nerve regeneration studies.
Keywords: facial nerve; electromyography; nerve regeneration; histologic analysis